Mendeteksi miskonsepsi bilangan bulat: Analisis proses berpikir mason berdasarkan kemampuan numerasi peserta didik - Prathiwi, Vhasshetha Indri; Maison, Maison; Huda, Nizlel (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
Students' low numeracy skills in understanding integer concepts often lead to misconceptions that frequently undetected, as they are embedded within students' cognitive processes rather than solely visible in final answers. This study aims to detect students' misconceptions in integer topics by analyzing their thinking processes using Mason's framework, based on their numeracy levels. This research employed a descriptive qualitative approach, involving six seventh-grade students from class VII at MTsN 8 Muaro Jambi. The subjects were classified into three numeracy categories: high, medium, and low. Data were collected through think-aloud-based diagnostic tests, in-depth interviews, and observations during problem-solving sessions. Data were then analyzed using Mason’s stages of thinking. The results showed that all students experienced theoretical and correlational misconceptions, while classification misconceptions were found only among students with low numeracy levels. Most errors occurred in the attack and review stages. Mason’s thinking framework proved effective in systematically identifying the location and type of misconceptions and provides a foundation for designing more targeted and responsive numeracy-based instructional strategies.